Existence of solutions for nonlinear integro-dynamic equations with mixed perturbations of the second type via Krasnoselskii’s fixed point theorem - Guerfi, A.; Ardjouni, A. (Methods of Functional Analysis and Topology, 2022)
We prove the existence of solutions of a nonlinear integro-dynamic equation with mixed perturbations of the second type on time scales. The main tool employed here is Krasnoselskii’s fixed point theorem. An example is given to illustrate the main results. Доведено існування розв’язків нелінійного інтегродинамічного рівняння зі змішаними збуреннями за часовою шкалою другого типу. Основним використаним інструментом є теорема Красносельського про нерухому точку. Наведено приклад для ілюстрації основних результатів.